Polymer-assisted co-precipitation route for the synthesis of Al2O3-13% TiO2 nanocomposite - Singh N.; Mazumder R.; Gupta P.; Kumar D. (My University, 2025)
The present investigation reveals the effect of processing parameters on the properties of alumina-titania (Al2O3-TiO2) nanocomposites. A polymer-assisted (Pluronic P123 triblock co-polymer) co-precipitation route has been employed to synthesize Al2O3-TiO2 nanoparticles. As a surfactant, pluronic P123 polymer exhibits hydrophobic as well as the hydrophilic nature simultaneously which detains the agglomeration and hence the nano size particle have been obtained. Effect of surfactant concentration on morphology and particle size of product has also been investigated. Thermal behaviour of the prepared powder samples have been studied using differential scanning calorimeter/thermal gravimetric analysis and dilatometer. Formation of aluminium-titanate (Al2TiO5) phase has been confirmed using X-ray diffraction analysis. It has been observed by field emission scanning electron microscopy analysis that the particle size reduced effectively (below 100 nm) when polymer-assisted co-precipitation route is used instead of the simple co-precipitation technique. A highly dense microstructure of sintered samples has been obtained, driven by reduced particle size. © Indian Academy of Sciences.